1997
DOI: 10.1002/masy.19971190133
|View full text |Cite
|
Sign up to set email alerts
|

13C, 25Mg and 11B solid‐state NMR study of a fire retarded ethylene‐vinyl acetate copolymer

Abstract: Flame retardance of ethylene‐vinyl acetate copolymer (EVA) can be achieved using magnesium hydroxide (Mg(OH)2) incorporated in the polymeric matrix. The adduct of small amount of zinc borate as synergistic agent in the formulation increases the fire‐proofing properties. Multinuclei solid‐state NMR appears as a powerful means to characterise materials before and after combustion. We show that endothermic dehydration, water vapour evolved and formation of a glassy coating provide the flame retardancy of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The band assigned to CH is detected at 72 ppm [20]. The chemical shift at 170 ppm corresponding to C=O in the acetate group is not observed (except a tiny band for EVA-AP760, (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
See 1 more Smart Citation
“…The band assigned to CH is detected at 72 ppm [20]. The chemical shift at 170 ppm corresponding to C=O in the acetate group is not observed (except a tiny band for EVA-AP760, (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…The non-degraded materials (t 0 ) with and without ZnCO 3 show the same 13 C NMR spectra. The resonance band at 21 ppm corresponds to the CH 3 -group of the acetic acid functionality of EVA [20]. The bands at 25, 30 and 35 ppm are attributed to the CH 2 -groups in the polymer backbone [21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…39 25 Mg NMR has been used to investigate the role of Mg(OH) 2 as a fire retardant in ethylene-vinyl acetate copolymers. 147 The very significant change in the lineshape indicated that on combustion a glassy phase was formed that was the source of the retarding action. 25 Mg NMR has been used to study the thermal decomposition of Mg(OH) 2 to MgO.…”
Section: Oxide-based Crystalline Inorganic Materialsmentioning
confidence: 98%
“…The spectrum corresponds to the data reported already in the literature for pure EVM. 17,[26][27][28][29][30] The peak at 20.8 ppm corresponds to the CH 3group of the acetic acid functionality of the polymer. 28 Those at 25.1, 29.8 and 34.5 ppm are attributed to the CH 2 -groups in the polymer backbone.…”
Section: The Decomposition Mechanismmentioning
confidence: 99%
“…17,[26][27][28][29][30] The peak at 20.8 ppm corresponds to the CH 3group of the acetic acid functionality of the polymer. 28 Those at 25.1, 29.8 and 34.5 ppm are attributed to the CH 2 -groups in the polymer backbone. 27,31 The multiplicity of the peaks is due to the fact that when the VA monomer copolymerizes with ethylene, a random copolymer is obtained leading to several different monomer sequences in the chain.…”
Section: The Decomposition Mechanismmentioning
confidence: 99%